2022
DOI: 10.3390/ijms232214479
|View full text |Cite
|
Sign up to set email alerts
|

Salivary microRNA and Metabolic Profiles in a Mouse Model of Subchronic and Mild Social Defeat Stress

Abstract: Identification of early biomarkers of stress is important for preventing mood and anxiety disorders. Saliva is an easy-to-collect and non-invasive diagnostic target. The aim of this study was to characterize the changes in salivary whole microRNAs (miRNAs) and metabolites in mice subjected to subchronic and mild social defeat stress (sCSDS). In this study, we identified seven upregulated and one downregulated miRNAs/PIWI-interacting RNA (piRNA) in the saliva of sCSDS mice. One of them, miR-208b-3p, which is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
1
1
0
1
Order By: Relevance
“…Therefore, the increase in brain lactate levels in CSD mice seemed to be caused by chronic sleep impairment and not by awakening. Others have found contradictory effects of lactate levels between the brain and saliva in mouse models of social defeat stress 41 , 45 ; the present findings were similar. Salivary lactate appears to be derived from host circulation via the salivary glands rather than microbes, because lactate concentrations are identical between whole mouth and parotid saliva 46 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, the increase in brain lactate levels in CSD mice seemed to be caused by chronic sleep impairment and not by awakening. Others have found contradictory effects of lactate levels between the brain and saliva in mouse models of social defeat stress 41 , 45 ; the present findings were similar. Salivary lactate appears to be derived from host circulation via the salivary glands rather than microbes, because lactate concentrations are identical between whole mouth and parotid saliva 46 .…”
Section: Discussionsupporting
confidence: 89%
“…However, we also identified an unusual metabolic profile in a participant with a PSQI of 6, which was considerably higher than of the others (PSQI ≤ 3; data not shown). Furthermore, salivary metabolites except for lactate were only slightly affected in a mouse model of social defeat stress 41 . These results suggested that serious sleep disorders affect salivary metabolic profiles whereas simple sleep restriction or a depression-like state does not.…”
Section: Discussionmentioning
confidence: 93%
“…Было установлено, что микроРНК участвуют в различных биологических процессах в центральной нервной системе, включая рост и развитие нейронов, синаптическую пластичность и передачу нервных импульсов с помощью нейромедиаторов, которые имеют непосредственное отношение к психическим функциям животных и человека [11,12]. В последние годы микроРНК активно исследуются как потенциальные биомаркеры психологического статуса [13][14][15][16][17][18][19][20] и психических расстройств [21][22][23][24].…”
Section: Introductionunclassified